Systemy informacyjne monitoringu bezpieczeństwa żywności - Matolicz, Krzysztof (Information Systems that Monitor Safety of Food, 2007)
The aim of this paper is to present informatics systems which help keep the food safe. Two types of mutually exclusive systems were chosen. The first is RASFF which is used by the European Union countries. The second are systems which help industry fill tracing back and tracing forward rules. The paper expands knowledge about this kind of systems and improves choosing a food monitoring system for companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 317-325